Gut microbiome lipid metabolism and its impact on host physiology - Brown, Eric M.; Clardy, Jon; Xavier, Ramnik J. (Cell host & microbe, 2023)
Metabolites produced by commensal gut microbes impact host health through their recognition by the immune system and their influence on numerous metabolic pathways. Notably, the gut microbiota can both transform and synthesize lipids as well as break down dietary lipids to generate secondary metabolites with host modulatory properties. Although lipids have largely been consigned to structural roles, particularly in cell membranes, recent research has led to an increased appreciation of their signaling activities, with potential impacts on host health and physiology. This review focuses on studies that highlight the functions of bioactive lipids in mammalian physiology, with a special emphasis on immunity and metabolism. Synthesis, ingestion, and absorption of lipids is essential for human life and is a process mediated by the gut microbiome. Alterations in lipid signaling pathways are behind numerous diseases. Here, Brown and colleagues describe the recent literature on the lipids that microbiome species can synthesize and their function on host physiology.